Immunomodulatory Effects of Male Papaya Leaf Extract (Carica papaya L.) on Interferon-gamma and Interleukin-6 Levels in an In Vivo Viral Infection Model - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Viral infections pose a significant challenge to global health due to their ability to disrupt immune homeostasis and trigger excessive inflammatory responses. Immunomodulatory agents that enhance antiviral immunity while controlling inflammation are therefore essential. This study aimed to evaluate the immunomodulatory effects of male papaya leaf extract (Carica papaya L.) on Interferon-gamma (IFN-gamma) and Interleukin-6 (IL-6) levels in an in vivo viral infection model. Male papaya leaves were extracted using 70% ethanol and administered orally to virus-infected Wistar rats at two different doses for 14 days. Serum levels of IFN-gamma and IL-6 were measured using enzyme-linked immunosorbent assay (ELISA). The results demonstrated that viral infection significantly decreased IFN-gamma levels and increased IL-6 levels compared to the normal control. Treatment with male papaya leaf extract resulted in a dose-dependent increase in IFN-gamma and a significant reduction in IL-6 levels compared to the negative control group. The high-dose extract group showed the most pronounced immunomodulatory effect, comparable to or exceeding that of the positive control. These findings indicate that male papaya leaf extract has potential as a natural immunomodulatory agent by enhancing antiviral immune responses and suppressing excessive inflammation. Further studies are recommended to explore its molecular mechanisms and therapeutic applications.